Clinical significance of pulmonary nodules in decision-making and management of patients diagnosed with esophageal cancer. Issue 3 (25th October 2019) - Dellaportas, D; Laliotis, A; Zylstra, J; Davies, A; Gossage, J A
SUMMARY: In esophageal cancer, metastatic spread to the lungs is detected in 4–9.7% of cases. During staging investigations, 22% of patients have pulmonary nodules detected on cross-sectional imaging. The purpose of this study is to elucidate the clinical importance of these incidentally found pulmonary nodules, in patients with clinically localized esophageal cancer. A retrospective cohort study was conducted from January 2008 to December 2012 in a tertiary esophagogastric referral center. One-hundred and forty-nine patients were included in the study. All patients underwent dedicated staging followed by neoadjuvant chemotherapy and surgery as indicated. Thirty-three (22.1%) patients had pulmonary nodules found in their preoperative staging. Only three (9%) patients proved to develop metastatic pulmonary disease on follow-up. Interestingly, in all three patients, the nodules were negative on initial 18− fluorodeoxyglucose positron emission tomography. Incidentally found pulmonary nodules in newly diagnosed patients with esophageal cancer during staging investigations are rarely metastases. Such nodules, in isolation, should not preclude patients from radical treatment.